2023
DOI: 10.1016/j.jvoice.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Famotidine and Other Acid Reflux Medications for SARS-CoV-2: A Pilot Study

Abstract: Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus-19 disease pandemic. The H-2 blocker famotidine has been suggested as an FDAapproved drug that could potentially be repurposed for treatment of COVID-19. Famotidine has since been shown to improve patient outcomes and reduce symptom severity in patients acutely ill with COVID-19. Other studies have suggested that proton pump inhibitors (PPIs) might have an association with COVID-19. Objective. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…A case series of 10 non-hospitalized COVID patients reported improved symptoms score after initiation of high dose famotidine [ 26 ]. However, a survey study conducted in otolaryngology patients found that chronic famotidine use was not associated with incidence of COVID-19 [ 27 ]. Regardless, higher quality studies such as RCTs are needed to further elucidate the role of famotidine in treating mild to moderate, non-hospitalized COVID-19 patients, and one such study is currently underway at Northwell Health [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A case series of 10 non-hospitalized COVID patients reported improved symptoms score after initiation of high dose famotidine [ 26 ]. However, a survey study conducted in otolaryngology patients found that chronic famotidine use was not associated with incidence of COVID-19 [ 27 ]. Regardless, higher quality studies such as RCTs are needed to further elucidate the role of famotidine in treating mild to moderate, non-hospitalized COVID-19 patients, and one such study is currently underway at Northwell Health [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perubahan pola pembelajaran yang terjadi pada sektor pendidikan akibat Covid-19 (Balouch, 2021& Yasenov, 2020 sangat signifikan dari proses belajar mengajar sempat terhenti hingga muncul trens pembelajaran daring yang dikeluarkan oleh pemerintah pusat dengan skema pembelajaran dibagi berdasarkan zona aman hingga zona merah orang yang terpapar pandemi covid-19 (Lau et al, 2021;Malyana, 2020;Putro, 2020). Hingga pada tahun 2021 pemerintah masih menghimbau kepada satuan pendidikan untuk menerapkan pembelajaran jarak jauh meskipun anak sudah tidak betah untuk belajar dirumah (Wiguna, 2020).…”
Section: Pendahuluanunclassified
“…Furthermore, using the following agents in the order of preference based on efficacy is recommended in patients at risk of progression to severe COVID-19: ritonavir-boosted nirmatrelvir, sotrovimab, remdesivir, and molnupiravir [ 8 ]. The H-2 blocker, famotidine, has been suggested as an FDA-approved drug that could potentially be repurposed for the treatment of COVID-19 [ 9 ]. Famotidine has since then been shown to improve patient outcomes and reduce symptom severity in patients acutely ill with COVID-19 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The H-2 blocker, famotidine, has been suggested as an FDA-approved drug that could potentially be repurposed for the treatment of COVID-19 [ 9 ]. Famotidine has since then been shown to improve patient outcomes and reduce symptom severity in patients acutely ill with COVID-19 [ 9 ]. Mather et al observed that in-hospital death, intubation, and combined death/intubation were significantly lower in the famotidine group than the non-famotidine group [ 10 ].…”
Section: Introductionmentioning
confidence: 99%